Adicción de un adolescente de 14 años e incidencia en una familia del cantón Jujan - Gómez Muñoz, José Geremías (2021)
The use and consumption of illegal drugs is a problem that has caused years of suffering in families and much more in those homes with greater vulnerability; it is a plague that is immersed in society and that affects young people with greater determination, as it is the most flexible, unstable and impressionable group of the population due to its weak character. Therefore, the main factor in this case study was the family of the adolescent who was consuming psychotropic substances, an event that the members of the household already suspected. This situation generated an urgent psychotherapeutic intervention for the adolescent individually and with his family, using instruments such as direct observation, psychometric test (DAST-10), cognitive behavioral techniques, to help improve the behavior of the young man who was affected by addiction.